2001
DOI: 10.1034/j.1600-0838.2001.110505.x
|View full text |Cite
|
Sign up to set email alerts
|

Tests for physical function of the elderly with knee and hip osteoarthritis

Abstract: This study reports the results of a battery of physical function tests used to assess physical function of older patients with clinical knee and/or hip osteoarthritis (OA), and the correlation to the WOMAC Index (disease-specific questionnaire). A total of 106 sedentary subjects, aged >60 years (mean 69.4, S.D. 5.9) with hip and/or knee OA (mean 12.2 yrs, S.D. 11.0) participated in the study. Mobility, joint flexibility and muscle strength were evaluated by recording time to: walk a distance of 8', ascend/desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
119
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(125 citation statements)
references
References 0 publications
4
119
2
Order By: Relevance
“…These findings are consistent with previous research which found moderate to strong (> 0.4) correlations with the WOMAC function and stair climbing, walking or the get-up-and-go test. [319][320][321][322][323] Moderate to strong correlations have also been reported pre-operatively between the WOMAC function and the HHS or its components, 319,321,324 and small to moderate correlations have been found between the WOMAC function and the AKSS. 319,325,326 Our finding of a strong relationship between the Ab-A and WOMAC function score is not surprising as the Ab-A is based on several items of the WOMAC.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with previous research which found moderate to strong (> 0.4) correlations with the WOMAC function and stair climbing, walking or the get-up-and-go test. [319][320][321][322][323] Moderate to strong correlations have also been reported pre-operatively between the WOMAC function and the HHS or its components, 319,321,324 and small to moderate correlations have been found between the WOMAC function and the AKSS. 319,325,326 Our finding of a strong relationship between the Ab-A and WOMAC function score is not surprising as the Ab-A is based on several items of the WOMAC.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have arrived at discordant conclusions about the relationship between function and ROM. Some reports suggest that ROM is an important determinant of function 321,329 while others disagree. 317,338 Furthermore, it is suggested that ROM is important for some specific functions, or that a threshold of around 95-100°of flexion is required for adequate function.…”
Section: Discussionmentioning
confidence: 99%
“…Table 6. Functional Assessment System (FAS) 140 Lin battery 115 Steultjens battery 174 Stratford battery 177 Site-specific physical functioning…”
Section: Assessment Of Function24mentioning
confidence: 99%
“…10 Investigation of minimal clinically important differences (MCIDs) of physical performance measures is warranted, as these have become commonly used outcome measures in the treatment of OA. 8,12,17,[35][36][37] At present, the responsiveness (in terms of MCID) of the timed up-and-go (TUG) test, 40-meter self-paced walk test (40-m SPWT), 30-second chair stand (30 CST), and 20-cm step test has not been investigated in T T STUDY DESIGN: Prospective cohort study. …”
mentioning
confidence: 99%